Optimization of Personal Grooming and Attitudes for Hospitality Internship Preparation at SMKN 2 Sukawati - Sudarmini, Ni Luh; Sutarya, I Gede; Kiriana, I Nyoman (Darul Yasin Al Sys, 2025)
This study addresses the limited research on the impact of Field Work Practice (Praktik Kerja Lapangan, PKL) on the development of students' personal attitudes and physical appearance, despite PKL’s critical role in preparing vocational high school students for professional environments. The objective of this study is to analyze the influence of PKL on behavioral changes, specifically in areas such as discipline, cooperation, responsibility, appearance, and communication. Employing a quantitative research design, the study involved 60 vocational high school students in Indonesia, selected through purposive sampling. Data were collected using structured observation sheets and teacher evaluation questionnaires administered before and after the PKL period. Descriptive statistics and comparative analysis techniques were used to analyze the data. The findings indicate a significant improvement in students’ attitudes and physical appearance following their PKL experiences. Notable enhancements were observed in indicators such as neatness, politeness, initiative, and responsibility. These outcomes align with experiential learning theories, which emphasize the value of real-world engagement in fostering student development. The study concludes that PKL is instrumental in character formation and the enhancement of practical skills, affirming the importance of integrating workplace-based learning into vocational education curricula. Theoretically, the study contributes to the expanding body of literature on experiential learning and character development in vocational education. Practically, it provides valuable insights for educators and policymakers to strengthen the design, implementation, and evaluation of PKL programs. Future research is recommended to explore the varied impacts of PKL across different industry sectors and to include more diverse samples for broader generalizability.